Measurements of stratospheric hydrogen cyanide at McMurdo Station, Antarctica - Further evidence of winter stratospheric subsidence? - Jaramillo, M.; De Zafra, R. L.; Barrett, J.; Emmons, L. K.; Solomon, P. M. (1989)
Measurements of hydrogen cyanide in the springtime Antarctic stratosphere were made using ground-based millimeter wave spectroscopy. A steeper decrease in volume mixing ratio with altitude was found, than that found at tropical latitudes, from an assumed value of about 160 pptv in the troposphere to a value of 65 + or - 30 pptv at 40 km, which may be further evidence of substantial vertical subsidence of the Antarctic winter stratosphere.